Melting behaviour of americium-doped uranium dioxide. (June 2016) - Prieur, D.; Lebreton, F.; Caisso, M.; Martin, P.M.; Scheinost, A.C.; Delahaye, T.; Manara, D.
Graphical abstract: Highlights: First study on the melting of americium-doped uranium dioxide. The laser melted materials have been characterised by XRD and XAS. For low x(AmO2 ), the (U, Am)O2 solidus line follows the ideal solution behaviour. Measured solidus points are between 3051 K and 3070 K for 0.12. Abstract: (Uranium + americium) mixed oxides are considered as potential targets for americium transmutation in fast neutron reactors. Their thermophysical properties and notably their melting behaviour have not been assessed properly although required in order to evaluate the safety of these compounds under irradiation. In this study, we measured via laser heating, the melting points under inert atmosphere (Ar) of U1− x Am x O2± δ samples with x  = 0.10, 0.15, 0.20. The obtained melting/solidification temperatures, measured here, indicate that under the current experimental conditions in the investigated AmO2 content range, the solidus line of the (UO2  + AmO2 ) system follows with very good agreement the ideal solution behaviour. Accordingly, the observed liquidus formation temperature decreases from (3130 ± 20) K for pure UO2 to (3051 ± 28) K for U0.8 Am0.2 O2± δ . The melted and quenched materials have been characterised by combining X-ray diffraction and X-ray absorption spectroscopy.